2022
DOI: 10.23889/ijpds.v7i1.1689
|View full text |Cite
|
Sign up to set email alerts
|

Describing the linkage between administrative social assistance and health care databases in Ontario, Canada

Abstract: BackgroundThe linkage of records across administrative databases has become a powerful tool to increase information available to undertake research and analytics in a privacy protective manner. ObjectiveThe objective of this paper was to describe the data integration strategy used to link the Ontario Ministry of Children, Community and Social Services (MCCSS)-Social Assistance (SA) database with administrative health care data. MethodsDeterministic and probabilistic linkage methods were used to link the MCCSS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Thus, linking social care data to healthcare data shows potential for integrated governance, but there are also known pitfalls. A Canadian study linking administrative social assistance data to healthcare data warns for potential biases due to linkage errors 17. A study in Dundee, Scotland found that linkage between health and social care data faced challenges around data linkage (eg, use of a shared identifier across organisations), data analysis (eg, understanding missing data) and the need for tacit knowledge (eg, people understanding the data, its limitations and what it represents) limiting the full exploitation 18.…”
Section: Introduction (Background and Problem Statement)mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, linking social care data to healthcare data shows potential for integrated governance, but there are also known pitfalls. A Canadian study linking administrative social assistance data to healthcare data warns for potential biases due to linkage errors 17. A study in Dundee, Scotland found that linkage between health and social care data faced challenges around data linkage (eg, use of a shared identifier across organisations), data analysis (eg, understanding missing data) and the need for tacit knowledge (eg, people understanding the data, its limitations and what it represents) limiting the full exploitation 18.…”
Section: Introduction (Background and Problem Statement)mentioning
confidence: 99%
“…A Canadian study linking administrative social assistance data to healthcare data warns for potential biases due to linkage errors. 17 A study in Dundee, Scotland found that linkage between health and social care data faced challenges around data linkage (eg, use of a shared identifier across organisations), data analysis (eg, understanding missing data) and the need for tacit knowledge (eg, people understanding the data, its limitations and what it represents) limiting the full exploitation. 18 The Integrated Children’s System in the UK initially followed a top-down managerial approach emphasising on accountability of institutional risk instead of user-centredness which had a detrimental effect on professional autonomy.…”
Section: Introduction (Background and Problem Statement)mentioning
confidence: 99%